Evaluating the Effectiveness of a Pragmatic Intervention in Reducing Blood Pressure in Patients with Hypertension. (June 2015) - Chia, Yook Chin; Liew, Su May; Lee, Ping Yein; Abdullah, Adina; Abdullah, Nurdiana; Hanafi, Nik Sherina; Ng, Chirk Jenn; Wong, Stalia Siew Lee; Zaidi, Nur Farhana Mohd; Khoo, Ee Ming
Abstract : Background: Implementation of guidelines in hypertension remains challenging in primary care. Interventions are needed to improve hypertension management using guidelines. Objectives: To evaluate effectiveness of an intervention using guidelines in reducing blood pressure in patients with hypertension. Method: This before-and-after study was conducted in a primary care clinic for six months. The intervention involved professional training, availability of hypertension guideline and structured format of medical notes for hypertension. Primary outcome is the change in proportion of patients with uncontrolled BP (SBP ≥ 140 mmHg and/or DBP ≥ 90 mmHg) and secondary outcome is the mean BP change at 6 months. Results: A total of 555 patients were recruited. At baseline, 227/555 (40.9%) had uncontrolled BP. By 6 months 186/463 (40.2%) was uncontrolled. Among those with uncontrolled BP at baseline, 51.8% had BP controlled at 6 months; SBP in the uncontrolled group decreased from 147.8 (11.2) to 138.8 (15.2) mmHg ( p  < 0.001, CI: 6.6, 11.4); DBP decreased from 83.7 (8.0) to 79.6 (8.3) mmHg ( p  < 0.001, CI: 2.610, 5.493). Among those with controlled BP, 34.4% became uncontrolled at 6 months. For the controlled group, the SBP in the controlled group increased from 125.8 (7.4) to 133.6 (12.8) mmHg ( p  < 0.001, CI: −9.475, −6.155); DBP increased from 75.6 (6.1) to 77.5 (7.4) mmHg ( p  < 0.001, CI: −2.984, −0.897). Conclusion: Although there was no change in the proportion of patients with uncontrolled BP, there was a significant reduction in mean BP of 9/4 mmHg in those with uncontrolled BP. Patients with controlled BP still need continuous monitoring.